THE EFFECTS OF METHANOLIC LEAF EXTRACT OF GONGRONEMA LATIFOLIUM ON MILK YIELD AND SOME LACTOGENIC HORMONES IN LACTATING WISTAR RATS - Ogbonna, Grace; Magaji, Rabiu; Isa, Sherif (FUDMA JOURNAL OF SCIENCES, 2022)
Proper and exclusive breastfeeding is recommended during the early infancy stage of a child. Lactation insufficiency serves as a hinderance to this. Gongronema latifolium is an important medicinal plant known for its various therapeutic effects. The lactogenic effects of Gongronema latifolium used locally to boost lactation was investigated. Twenty Wistar dams were grouped into five groups (n=4); consisting of control group (1 ml/kg distilled water), standard drug group (metoclopramide 5 mg/kg), 200 mg /kg, 400 mg/kg and 800 mg/kg Gongronema latifolium methanolic extract groups. The pups were weighed 18 hours after the administration of Gongronema latifolium orally, to assess milk yield while the serum was gotten from the dams on the ninth day of administration. Toxicity study showed that the plant extract was non-toxic (LD50 > 5000 mg/kg) when administered orally. The leaf extract significantly increased the serum prolactin (p< 0.05). There was also significant increase in the milk yield in the group administered with Gongronema latifolium group versus the control group (7.28 ± 1.15 g/pup, 7.33 ± 1.08 g/pup and 9.68 ± 0.97 g/pup vs 5.5 ± 1.01 g/pup respectively). These lactogenic effects were also dose- dependent. The leaf extract had no significant effect on the oxytocin serum concentration of the lactating Wistar rats. The lactogenic effect Gongronema latifolium may be ascribed to the presence of phytochemicals such as Saponins (e.g., diosgenin, kaempferol, quercetin and silybin) that have phytoestrogenic effects that could promote milk synthesis, secretory differentiation and mammary epithelial cells proliferations.